Gilbert M. Hitchcock papers - Hitchcock, Gilbert M. (Gilbert Monell), 1859-1934.
Correspondence, memorandum, reports, and printed material pertaining to Hitchcock's service as in the U.S. Senate. Papers (1917-1920) as chairman of the Senate Committee on Foreign Relations shed light on the relations between President Woodrow Wilson and Congress especially during the treaty fight in the Senate, 1919-1920. Includes Hitchcock's correspondence with the President and with Edith Bolling Galt Wilson on behalf of her husband. Other correspondents include Newton Diehl Baker, Robert Lansing, and William H. Taft.
Microfilm edition available in part
Microfilm produced from originals in the Manuscript Division.
In part, transcripts.
U.S. senator and newspaper publisher from Nebraska.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Baker, Newton Diehl, -- 1871-1937 -- Correspondence; Lansing, Robert, -- 1864-1928 -- Correspondence; Taft, William H. -- 1857-1930 -- Correspondence; Wilson, Edith Bolling Galt, -- 1872-1961 -- Correspondence; Wilson, Woodrow, -- 1856-1924 -- Correspondence; United States. -- Congress; United States. -- Congress. -- Senate. -- Committee on Foreign Relations; United States -- Politics and government -- 1913-1921.; Publishers; Senators, U.S., Congress -- Nebraska